THE ANALYSIS OF TEACHER’S BELIEF ON DIGITAL LITERACY IN FORIGN LANGUAGE TEACHING - Muhamad Taufik Hidayat (Institut Pendidikan Indonesia Garut, 2019)
Digital literacy is a substantial part of 21st-century learning every teachers need to possess. Consequently, the rapid development of digital technologies requires teachers as learning architects and instigators to employ digital literacy in organizing their students in digital environments. In spite of its importance, research related to teachers’ digital literacy in English Language Teaching context is limited. Hence, this study aims to explore more on teachers’ belief about the integration of digital literacy through three aspects of teacher’s belief; behavioral belief, normative belief and control belief. For that reason, a qualitative analysis on English teachers was employed in this research. Five English in-service teachers were examined through interviews as the data collecting techniques. The findings indicated that the behavioral belief was related to the implementation of the concept of digital literacy in terms of developing students’ 21st-century skills, normative belief dealt with the expectation in social context both administrators and parents, while control belief was about the availability of particular digital technology to be implemented in the classroom. The findings of this study expected to provide an overview of the teacher’s belief which drives the integration of digital literacy in the classroom. This study provides an overview of teachers’ beliefs in integrating digital literacy which help teachers to personalize their professional development to adjust the digital era into teaching-learning instructions.